Patterns of Seismicity Associated with USGS Identified Areas of Potentially Induced Seismicity. Issue 1 (30th March 2018) - Barnes, Caitlin; Halihan, Todd
Abstract: A systematic review across U.S. Geological Survey (USGS) identified potentially induced seismic locations was conducted to discover seismic distance patterns and trends over time away from injection disposal wells. Previous research indicates a 10 km (6 miles) average where the majority of induced seismicity is expected to occur within individual locations, with some areas reporting a larger radius of 35 km (22 miles) to over 70 km (43 miles). This research analyzed earthquake occurrences within nine USGS locations where specified wells were identified as contributors to induced seismicity to determine distance patterns from disposal wells or outward seismic migration over time using established principles of hydrogeology. Results indicate a radius of 31.6 km (20 miles) where 90% of felt earthquakes occur among locations, with the closest proximal felt seismic events, on average, occurring 3 km (1.9 miles) away from injection disposal wells. The results of this research found distance trends across multiple locations of potentially induced seismicity. Abstract : Article Impact Statement: This systematic analysis of potentially induced seismic areas found patterns between earthquake incidence and distance from injection wells.